The Phonological Word and Stress Shift in Northern Kurmanji Kurdish - Mohammed Hasan, Aveen (European Scientific Journal, ESJ, 2016)
It is generally believed that stress in Kurdish is word-final. However, closer examination reveals several kinds of exceptions. This study proposes a unified analysis of regular and irregular stress patterns in Northern Kurmanji. It analyses the stress-assignment rule on the basis of a framework of prosodic phonology that divides the representation of speech into hierarchically organised units. It proposes the phonological word as the domain of stress rule and a number of other phonological processes such as glide insertion, resyllabification, vowel deletion, vowel shortening. Additionally, it proposes the cyclic analysis as the method of the rule application. Cases of stress rule violation are considered as instances of stress-shift which are conditioned by different phonological and syntactical factors or they can be accounted for by using recursive structure and phrase stress rule.